Pengaruh Customer Engagement Melalui Media Sosial terhadap Kepercayaan Merek (Studi Kasus : Instagram Shopee) - Odytri Caesar Mahayani; Ismiarta Aknuranda; Ari Kusyanti (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Trust in brands can be grown from the reciprocal relationship in an engagement interaction. Customer engagement through social media is an attempt by a company to keep in touch with its customers through social media facilities. According to a survey Instagram is a social media with the highest involvement value. Shopee is one of the most popular marketplaces in Indonesia. Compared to other marketplaces, from March to May 2018 the number of Shopee followers on Instagram is very high, and in terms of Shopee engagement also has the highest level of engagement. Therefore this study aims to see whether customer engagement by Shopee through Instagram social media has been able to create trust in the Shopee brand. There are 4 variables used in this study in the effort to establish customer engagement. Data collection is done online by distributing questionnaires to followers of Shopee Indonesia Instagram accounts who have interacted with giving, commenting, and reposting Shopee Indonesia Instagram accounts at least 3 times to 100 respondents. This study aims to find a relationship from the existence of customer engagement to brand trust partially and simultaneously using multiple linear regression analysis. Based on the results of the analysis that has been done partially, of the four variables 3 of them have a significant influence on the trust of the Shopee brand. While the results of the analysis are simultaneously known all variables together influence the brand trust.